Detection of bacteraemia by the continuously monitoring BacT/Alert system. Issue 10 (October 1995) - Kennedy, G T; Barr, J G; Goldsmith, C
Abstract : AIMS--To analyse a continuously monitoring blood culture system with respect to the time to detection of various groups of organisms, their clinical importance, and the relative efficacy of the aerobic and anaerobic bottles. METHODS--Four thousand blood cultures were monitored and the information relating to the positive cultures was noted and analysed. RESULTS--Four hundred and seventy seven blood cultures were detected as positive, 81% (387/477) of which were detected within 48 hours. The most pathogenic organisms were detected in the shortest period, less pathogenic later and those generally regarded as contaminants last. Clinically important isolates were also detected earlier. Many positive blood cultures were detected in only one bottle of the set, even those regarded as clinically important. CONCLUSIONS--The management of continuously monitoring blood culture systems could be improved by considering time to detection trends. Clinicians should be aware of the relatively rapid detection of clinically important, positive blood cultures in relation to patient treatment.